Horizontal histological sections in the preliminary evaluation of basal cell carcinoma submitted to Mohs micrographic surgery, - Poliana Santin Portela; Danilo Augusto Teixeira; Carlos D'Aparecida Santos Machado; Maria Aparecida Silva Pinhal; Francisco Macedo Paschoal
Abstract Background: Mohs micrographic surgery is a surgical technique for the treatment of nonmelanoma skin cancer. Surgery begins by removing the visible tumor before excision of the tissue specimens for evaluation of the tumor margins. Objectives: To present a new way to evaluate the material obtained from debulking, by horizontal histological analysis of the fragment. Methods: Descriptive retrospective cross-sectional study based on the medical records and histological lamellae of patients with primary basal cell carcinomas smaller than 1.5 cm submitted to Mohs micrographic surgery and who had the visible tumor analyzed by horizontal histological sections. Results: The sample evaluated included 16 patients with lesions located on the face. Comparing the histopathological examinations of incisional biopsy in vertical sections and debulking in horizontal sections, there was agreement in seven cases. The histological analysis performed in horizontal sections allowed identification of the tumor site in 13 cases, and the relation between tumor and margin showed that in 11 cases, the lateral margin was compromised.Study limitations: The technique was better-applied in lesions smaller than 2 cm. Conclusion: Horizontal histological analysis of debulking has advantages for Mohs surgery, since it allows visualization of almost all tumor extension in the same view plane of the dermatoscopy, allowing better definition of the histological subtype, tumor site, and tumor/margin of lesions less than 1.5 cm.